(untitled) (IJAS Indian Journal of African Studies, 2022)
Africa is considered the poorest continent in the world, despite the fact that it is the richest in natural resources. Africa suffers from chronic maladministration and a lack of effective leadership. Governance and poor leadership are becoming the identities of the African subcontinent. Leadership issues in Africa are always viewed in the context of development. The lack of leadership is really a challenge in the 21st century, as the people of the African subcontinent must understand that honest leadership is very important for the socio-economic and political development of society. In this present paper, the study has been conducted based on the literature available on the reasons behind faulty leadership. Such faulty leadership is responsible for poverty and economic backwardness. In essence, the study is qualitatively oriented and mainly uses secondary data for analysis. This article primarily evaluated the factors responsible for poor leadership and the challenges related to it. The study also looked at the importance of democracy and attempted to find a link between healthy democracies, strong leadership, and African development crises.